Decarboxylative Oxidation of Carboxylic Acids Using Photocatalysis and Copper Catalysis - Zaman, Muhammad Kashif; Khan, Shah Nawaz; Cai, Yuanyuan; Sun, Zhankui (Synlett, 2023)
A decarboxylative oxidation of carboxylic acids was developed through visible-light-induced photocatalysis with molecular oxygen as a green oxidant and copper as a co-catalyst. This reaction worked smoothly on various type of acids, and could potentially be used in modifications of natural products. The high efficiency of this transformation was demonstrated on over 40 substrates.